MENERAPKAN FILOSOFI PENDIDIKAN ISLAM DARI AL-QUR'AN KE DALAM KELAS - Shabri Hatlah, Mohamad; Yahiji, Kasim; Hasbi , Muh. (Kopertis Region IV Jabar and Banten, 2026)
The urgency of strengthening Qur'anic values in the modern education system is becoming increasingly important in the midst of moral crises and spiritual disorientation of students in the era of globalization and digitalization. This research aims to analyze and implement the philosophy of Islamic education sourced from the Qur'an into classroom learning practices. The approach used is qualitative research with the library research method through thematic analysis of Qur'anic verses, classical and contemporary interpretations, and relevant modern research results. The results of the study show that the implementation of the philosophy of Islamic education includes three main dimensions, namely the spiritual dimension that fosters the awareness of monotheism and worship orientation; an intellectual dimension that develops the ability to reflect on revelation; and the moral-social dimension that shapes the morals, righteous deeds, and social responsibilities of students. These three dimensions form a holistic education framework that unites faith, knowledge, and charity, and is the basis for strengthening the character of the Qur'ani in the context of the Independent Curriculum. This research contributes to the development of the philosophy of Islamic education by emphasizing the importance of integrating spiritual, intellectual, and moral values in the formation of human beings. In conclusion, Islamic education oriented to the Qur'an is able to answer the moral and social challenges of modern society. Further research is recommended to conduct field studies to test the effectiveness of the application of Qur'anic values in the context of empirical learning.